Filling Some Knowledge Gaps in the Ecology of the Snouted Treefrog, Ololygon berthae (Anura: Hylidae) - Lezcano, Andrea Itatí (2024)
We studied the ecology of the Snouted Treefrog (Ololygon berthae), providing new insights into sexual size dimorphism, fecundity, reproductive activity pattern, age, growth, and diet. We examined a set of 86 specimens from multiple localities from Corrientes Province, Argentina. Ololygon berthae exhibited sexual size dimorphism, with females averaging larger and heavier than males. The reproduction of O. berthae occurred during at least two periods of reproductive activity: in spring (September-October) and in summer (February-March). Gravid females contained an average of 331.1 mature ova. Based on skeletochronology, both sexes reached sexual maturityat 1 y old, while males exhibited longevity of 4 y compared to 3 y in females. Growth patterns for body size of males and females fit the von Bertalanffy’s growth model well, with a tendency of females to reach a larger asymptotic size and higher growth coefficients than males, although these differences were not significant. Ololygon berthae showed a generalist diet and a sit-and-wait predation strategy. The consumption of terrestrial prey by O. berthae revealed terrestrial behavior that was unexpected for a scansorial species. Filling such knowledge gaps in the ecology of O.berthae improves the understanding of this species and could help determine if conservation actions are needed.